2012
DOI: 10.2147/jpr.s34429
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose reduction in CT-guided sacroiliac joint injections to levels of pulsed fluoroscopy: a comparative study with technical considerations

Abstract: BackgroundThe sacroiliac (SI) joint is frequently the primary source of low back pain. Over the past decades, a number of different SI injection techniques have been used in its diagnosis and therapy. Despite the concerns regarding exposure to radiation, image-guided injection techniques are the preferred method to achieve safe and precise intra-articular needle placement. The following study presents a comparison of radiation doses, calculated for fluoroscopy and CT-guided SI joint injections in standard and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…One study found that a change in CT parameters to lower radiation dose resulted in an 86% reduction in total DLP (from 1458 mGy⅐cm to 199 mGy⅐cm) for CT-guided spine injection procedures for pain. 17 Artner et al 18 demonstrated that the dose related to CTguided sacroiliac joint injections can be significantly reduced to levels of pulsed fluoroscopy without compromising needle placement into the joint. In this study, we found a significantly reduced radiation dose as expressed by CTDIvol and DLP in patients undergoing CTguided spine biopsies using a low-dose protocol compared with a regular-dose protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found that a change in CT parameters to lower radiation dose resulted in an 86% reduction in total DLP (from 1458 mGy⅐cm to 199 mGy⅐cm) for CT-guided spine injection procedures for pain. 17 Artner et al 18 demonstrated that the dose related to CTguided sacroiliac joint injections can be significantly reduced to levels of pulsed fluoroscopy without compromising needle placement into the joint. In this study, we found a significantly reduced radiation dose as expressed by CTDIvol and DLP in patients undergoing CTguided spine biopsies using a low-dose protocol compared with a regular-dose protocol.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] This type of protocol modification has also been used in CT-guided interventions to limit radiation dose when performing multiple scans during the procedure. 8,[15][16][17][18] Given the increased desire to reduce radiation dose to patients, we transitioned our protocols for CT-guided spine biopsies to use a lower dose. The purpose of this study was to demonstrate that a low-dose protocol for CT-guided spine biopsies is as effective in tissue sampling without an increase in procedural time or an increase in complication rates compared with our legacy higher-dose approaches.…”
mentioning
confidence: 99%
“…This is less than the 87% dose reduction demonstrated by Patel et al for musculoskeletal biopsies in the pediatric population and less than the 85-94% dose reductions achieved by Artner et al for spinal, periradicular, and sacroiliac joint injections [2,[5][6][7]. As we experienced no loss in procedural success, this suggests that we may have room to further decrease radiation doses.…”
Section: Discussionmentioning
confidence: 53%
“…The radiation dose of CT interventions can be decreased to the level of fluoroscopic interventions by using a low-dose protocol that eliminates acquisition of a topogram, minimizes both energy and tube current, and severely restricts the number of image acquisitions during needle placement (86)(87)(88). At institutions where interventional CT is a limited resource, CT-guided injections for pain management can be challenging to schedule if they must compete for scanner time with biopsy, oncologic ablation, and abscess drainage procedures.…”
Section: Risk and Risk Mitigationmentioning
confidence: 99%